Toward global paradigm change: Beyond the crisis of the liberal world order - Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2019)
This vision brief may be summarized by the following points. First, the crisis of the liberal world order arises from a misalignment of our social, economic and political domains of activity, along with a resulting destabilization of our physical environment. The integration of the global economy has generated problems that extend beyond our current bounds of social and political cooperation. Second, extending our social cooperation - on which basis our political cooperation can be extended as well - requires the creation of the appropriate moral narratives. These narratives must guide business strategies, public policies and civic activities. Third, these narratives must be supplemented by multilevel governance structures that address challenges at the scale - micro, meso and macro - at which these chal-lenges arise. Finally, past human experience in developing moral narratives, supported by multilevel governance structures, suggests guidelines for a future form of multilateralism that enables us to meet this challenge.
Keywords: A12; A13; A14; B55; F02; H11; 330; economy; polity; society; environment; liberal world order; social cooperation; multilevel governance; narratives